Exposure of sufficient edge sites on well-crystallized MoSe2 induced by nitrogen doping (Mo−Nx) for Pt: Enhanced co-catalytic activity and methanol tolerance for oxygen reduction. (15th September 2018) - Pan, Siyu; Cai, Zhuang; Yang, Liu; Tang, Bo; Xu, Xin; Chen, Hun; Ran, Lingling; Jing, Baojian; Zou, Jinlong
Abstract: To endow catalyst supports with excellent co-catalytic activity is an effective way to strengthen methanol-tolerance of Pt-based catalysts towards oxygen reduction reaction (ORR). In this study, nitrogen-doped molybdenum selenide/biomass-derived carbon (N-MoSe2 /BC) composite as a Pt-support/co-catalyst is prepared via a synchronous synthesis method to enhance methanol tolerance. The porous structure of N-MoSe2 /BC with N-doping can improve the exposure of coordinated Mo–Sex sites along MoSe2 edges and provide the oxygen diffusion channels to promote ORR activity. Pt-N-MoSe2 /BC (Pt, 5 wt.%) shows high activity (14.83 mA cm −2 ) and selectivity (4e − pathway) towards ORR, promising durability (11.9% decline) and excellent tolerance against methanol-crossover effects, which are superior to those of commercial Pt/C (10 wt.%). With the introduction of pyridinic N, graphitic N and Mo−Nx in MoSe2 /BC, more active sites on Pt (111) facets are activated to enhance charge transfer efficiency and ORR activity. Both N-species in BC and exposed edge sites in N-MoSe2 contribute to high methanol-tolerance and co-catalytic activity towards ORR. Therefore, the remarkable ORR activity is originated from the synergistic effects among well-distributed Pt, N-species, and active edge sites of MoSe2 . Design of porous (N)-MoSe2 /BC provides a promising direction for preparation of co-catalyst/support with strong methanol tolerance and ORR activity. Highlights: N-MoSe2 /BC is used as co-catalyst/support to enhance ORR kinetics for the first time. Rich edge sites induced by doping N in MoSe2 (Mo-Nx ) enhance co-catalytic activity. Pt-N-MoSe2 /BC shows remarkably higher methanol tolerance and durability than Pt/C. N-MoSe2 can limit methanol adsorption on Pt active sites to avoid methanol oxidation. An efficient four-electron ORR pathway in acidic medium is obtained by Pt-N-MoSe2 /BC.